2015
DOI: 10.3329/bjp.v10i2.22424
|View full text |Cite
|
Sign up to set email alerts
|

Studies of <i>in vitro</i> anti-prostate cancer potential of newer 1,2,4-triazolo-1,3,4-thiadiazines with different heteroaromatics

Abstract: <p>This study was aimed to evaluate anticancer potential of newer synthesize 1,2,4-triazolo[3,4-b]-1,3,4-thiadiazines and its derivatives. All newly furnished scaffolds were subjected to screening for their in vitro anticancer potential against DU-145 and PC-3 prostate cancer cell lines using SRB and MMT bioassays. The structures of final compounds were confirmed with the aid of FT-IR, <sup>1</sup>H NMR, <sup>13</sup>C NMR spectroscopy and CHN analysis. Bioassay studies suggested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…An isothiazole ring fused with the quinolone nucleus at position 2 and 3 was reported to improve the potency . Similar to the antibacterial quinolones, C4 carbonyl was reported to be essential for the activity; other studies revealed that substitution with an alkoxy group as well as substituted amino moieties at position 4 can produce potent anticancer agents . Substitution at position 5 can affect the steric configuration and planarity of the whole compound.…”
Section: Structural Requirements and Sar Of Anticancer Quinolonementioning
confidence: 99%
“…An isothiazole ring fused with the quinolone nucleus at position 2 and 3 was reported to improve the potency . Similar to the antibacterial quinolones, C4 carbonyl was reported to be essential for the activity; other studies revealed that substitution with an alkoxy group as well as substituted amino moieties at position 4 can produce potent anticancer agents . Substitution at position 5 can affect the steric configuration and planarity of the whole compound.…”
Section: Structural Requirements and Sar Of Anticancer Quinolonementioning
confidence: 99%
“…A series 1,2,4-triazolo[3,4- b ][1,3,4]thiadiazines ( 99 ) was prepared by Fan et al [ 70 ] and evaluated for their in vitro anticancer activity against two prostate cancer cell lines PC-3 and DU-145 using SRB (sulforhodamine B) and MTT (3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide) assay. All the synthesized compounds exhibited remarkable cytotoxicity against targeted cell lines with GI 50 values ranging from 12.0 to 32.5 μg ml −1 and 16.5–27.7 μg ml −1 against DU-145 and PC-3 cell lines, respectively.…”
Section: Pharmacological Properties Of 124-triazolo[34- B ][134]thiadiazinesmentioning
confidence: 99%
“…Position 4 carbonyl group was essential for quinolones antibacterial activity, substitution at this position abolish the activity [56]. However, other studies revealed that substitution with alkoxy and amino groups at this position gave potent anticancer agents [70,71]. Position 5: Substitutions at this position have a great influence on the planarity and structural configuration of quinolones, as well as, cell permeability and affinity of the drug to bind with the target [72].…”
Section: Structure Activity Relationships (Sar) Of Cytotoxic Quinolonesmentioning
confidence: 99%